2015
DOI: 10.1302/0301-620x.97b10.35724
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of lumbar spinal fusion surgery in obese patients

Abstract: The aim of this study was to determine whether obesity affects pain, surgical and functional outcomes following lumbar spinal fusion for low back pain (LBP). A systematic literature review and meta-analysis was made of those studies that compared the outcome of lumbar spinal fusion for LBP in obese and non-obese patients. A total of 17 studies were included in the meta-analysis. There was no difference in the pain and functional outcomes. Lumbar spinal fusion in the obese patient resulted in a statistically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 31 publications
2
44
0
1
Order By: Relevance
“…1,3,14,29 These findings may be attributable to patient positioning, soft-tissue dissection, and inefficient or absent specialized equipment to enable expedient surgical intervention. With respect to hospital stay, it is plausible that the higher prevalence of comorbid conditions seen in the obese group-for example, obstructive airway disease, hypertension, diabetes mellitus, and coronary artery disease-may complicate recovery and consequentially extend the hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,3,14,29 These findings may be attributable to patient positioning, soft-tissue dissection, and inefficient or absent specialized equipment to enable expedient surgical intervention. With respect to hospital stay, it is plausible that the higher prevalence of comorbid conditions seen in the obese group-for example, obstructive airway disease, hypertension, diabetes mellitus, and coronary artery disease-may complicate recovery and consequentially extend the hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…12,25,26,31 Systematic reviews have identified obesity as an independent risk factor for increased blood loss, prolonged operating time, and more frequent complications with lumbar fusion surgery. 1,10,14 While most studies have revealed either a higher complication rate or increased resource utilization, inferior clinical outcomes in obese patients have not been consistently demonstrated. 14,28 Despite the current lack of evidence, a tendency to favor less extensive, nonfusion procedures in obese patients is plausible given the historically higher postoperative complication rates associated with these patients.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To more fully explore in impact of obesity on the entire spine, Teraguchi et al [24] investigated the prevalence and distribution of intervertebral disc degeneration over the entire spine and found the age and obesity were associated with the presence of disc degeneration in all areas of the spine, indicating that obesity places stress across multiple regions of back. BMI and obesity have also been identified as a risk factor for adjacent segment diseases and post-operative complications among patients undergoing lumbar fusion for degenerative spine diseases [30,31,32,33,34,35,36,37,38,39,40]. Weight control before and after the surgery was observed to reduce the incidence of adjacent segment disease and improve the fusion surgery outcome [41,42].…”
Section: Introductionmentioning
confidence: 99%